Carbon nano tube-carbon plate loaded transition metal fluoride composite material as well as preparation method and application thereof

By using carbon nanotube-carbon sheet-load transition metal fluoride composite material as the positive electrode sulfur carrier in lithium sulfur batteries, the problem of volume expansion and poor conductivity of positive electrode sulfur in lithium sulfur batteries is solved, and efficient polysulfide conversion is achieved And battery performance improvement.

CN119240809APending Publication Date: 2025-01-03WEIFANG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411356921.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The volume expansion, poor conductivity and slow polysulfide kinetic conversion of positive electrode sulfur in existing lithium sulfur batteries lead to battery life attenuation and low Coulomb efficiency. The preparation methods of existing carbon nanotubes and carbon sheets are complex, requiring high temperature or template agents .

Method used

Using carbon nanotube-carbon sheet-loaded transition metal fluoride composite material, the transition metal salt, 2-methylimidazole and N-acetylglucosamine are used to perform segmented heat treatment in the presence of fluorine source to form a one-dimensional-two-dimensional structure The carbon nanotube-carbon sheet is loaded with transition metal fluoride, as the positive sulfur carrier of lithium sulfur batteries.

Benefits of technology

The preparation of carbon nanotube-carbon sheet structures at lower temperatures is achieved, which improves the catalytic performance of polysulfides and the overall performance of lithium-sulfur batteries, including high specific capacity and good rate performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240809A_ABST
    Figure CN119240809A_ABST
Patent Text Reader

Abstract

The invention provides a carbon nanotube-carbon plate loaded transition metal fluoride composite material as well as a preparation method and application thereof, and belongs to the technical field of electrode materials. The prepared imidazole metal organic framework compound and N-acetylglucosamine are subjected to segmented heat treatment and carbonization under the protection of a fluorine source and inert gas, and the prepared composite material has a one-dimensional-two-dimensional structure; the one-dimensional carbon tube can provide a sulfur storage space, and the two-dimensional carbon plate can provide more adsorption sites and a conductive network; the transition metal fluoride can serve as a catalytic activity center and can effectively catalyze conversion of polysulfide, the composite material serves as a lithium-sulfur battery positive electrode sulfur carrier, excellent lithium-sulfur battery performance can be obtained, and the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a carbon nanotube-carbon sheet loaded transition metal fluoride composite material and a preparation method and application thereof. Background Art

[0002] In recent years, the surging demand for electric vehicles and electronic devices has driven the development of advanced energy storage technologies. Lithium-sulfur batteries (LSBs) have a high energy density of 2600 Whkg -1 The theoretical energy density of sulfur, the non-toxicity of the positive electrode active material sulfur, its abundant resources, environmental friendliness, and its low cost and availability have become the research hotspots of the next generation battery system. However, the volume expansion of sulfur during the charge and discharge process, the poor kinetics of sulfur catalytic conversion, and the sulfur loss caused by the shuttle effect have always hindered the further development of LSBs. For example, the volume expansion of sulfur, poor conductivity, slow kinetic conversion of polysulfides generated during the reaction, and the polysulfides (Li2S x ) intermediates dissolve into the electrolyte, pass through the separator, diffuse to the negative electrode, and directly react with the metallic lithium at the negative electrode, resulting in a shuttle effect, which ultimately causes irreversible loss of effective substances in the battery, attenuation of battery life, low coulombic efficiency, and other problems. Therefore, it is crucial to select a suitable cathode sulfur carrier to achieve sulfur fixation and rapid sulfur conversion.

[0003] Carbon materials are currently the most common sulfur carriers. For example, one-dimensional carbon nanotubes can better accommodate the volume expansion of sulfur, and two-dimensional carbon sheets can effectively increase the active sites for sulfur fixation and conversion. However, the growth of carbon nanotubes in the prior art usually requires a higher reaction temperature (>700°C), and the construction of carbon sheets usually requires the presence of a template (Fan et al. A Laid-Nanospace-Confinement Strategy for the Synthesis of Two-Dimensional Porous Carbon Nanosheets for High-Rate Performance Supercapacitors Advanced Energy Materials 2015, 5, 201401761). Therefore, how to prepare a positive electrode sulfur carrier by a relatively simple method (lower carbonization temperature, no template, etc.) to improve the catalytic performance of polysulfides still faces huge challenges. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon nanotube-carbon sheet loaded transition metal fluoride composite material and its preparation method and application. The composite material has both a one-dimensional and a two-dimensional structure and can be used as a positive electrode sulfur carrier of a lithium-sulfur battery to obtain excellent lithium-sulfur battery performance, and the preparation method is simple.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a carbon nanotube-carbon sheet-loaded transition metal fluoride composite material, comprising the following steps:

[0007] Mixing a transition metal salt, 2-methylimidazole and an organic solvent for coordination to obtain an imidazole metal organic framework compound; the transition metal salt includes a cobalt salt;

[0008] The imidazole metal organic framework compound and N-acetylglucosamine are mixed, and after segmented heat treatment in the presence of a fluorine source, carbonization is performed to obtain a carbon nanotube-carbon sheet-loaded transition metal fluoride composite material;

[0009] The staged heat treatment includes a first heat treatment and a second heat treatment performed sequentially; the temperature of the first heat treatment is 250-300°C; the temperature of the second heat treatment is 420-450°C.

[0010] Preferably, the transition metal salt further comprises one of a nickel salt, an iron salt and a zinc salt.

[0011] Preferably, the molar ratio of the transition metal salt to 2-methylimidazole is 1:4-8.

[0012] Preferably, the coordination temperature is room temperature and the time is 12 to 24 hours.

[0013] Preferably, the mass ratio of the imidazole metal organic framework compound to N-acetylglucosamine is 1:4-8.

[0014] Preferably, the fluorine source includes polytetrafluoroethylene; and the mass ratio of the imidazole metal organic framework compound to the fluorine source is 1:6-15.

[0015] Preferably, the first heat treatment time is 1 to 2 hours; the second heat treatment time is 2 to 3 hours.

[0016] Preferably, the carbonization temperature is 550-600° C. and the time is 2-4 hours.

[0017] The present invention provides a carbon nanotube-carbon sheet loaded transition metal fluoride composite material prepared by the preparation method described in the above technical solution.

[0018] The present invention provides application of the carbon nanotube-carbon sheet loaded transition metal fluoride composite material described in the above technical solution in a lithium-sulfur battery.

[0019] The invention provides a method for preparing a carbon nanotube-carbon sheet-loaded transition metal fluoride composite material. The N-acetylglucosamine used in the invention can be used as a supplementary carbon source and nitrogen source to inhibit nitrogen loss of a final product, and can also be used as a sacrificial template to induce an imidazole metal organic framework compound (MIF) to form a low-dimensional structure without the need for an external template agent. The segmented temperature increase heat treatment used in the invention can effectively utilize the characteristics of each component, thereby achieving carbonization at a relatively low temperature (below 600° C.), and better controlling material growth, so that N-acetylglucosamine and MIF are used together as carbon sources to form a carbon nanotube-carbon sheet-loaded transition metal fluoride having both a one-dimensional and two-dimensional structure. The prepared one-dimensional carbon tube can provide a sulfur storage space, and the two-dimensional carbon sheet can provide more adsorption sites and a conductive network. The transition metal fluoride can be used as a catalytic active center to effectively catalyze the conversion of polysulfide, thereby obtaining excellent lithium-sulfur battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the SEM image of the one-dimensional-two-dimensional carbon nanotube / carbon sheet loaded with CoF2 in Example 3;

[0021] Figure 2 The XRD pattern of the one-dimensional-two-dimensional carbon nanotube / carbon sheet loaded with CoF2 in Example 3;

[0022] Figure 3 The charge and discharge curve of the battery composed of the material of the one-dimensional-two-dimensional carbon nanotube / carbon sheet loaded with CoF2 in Example 3;

[0023] Figure 4 This is a rate performance diagram of a battery composed of a one-dimensional-two-dimensional structured carbon nanotube / carbon sheet loaded with CoF2 material in Example 3. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a carbon nanotube-carbon sheet-loaded transition metal fluoride composite material, comprising the following steps:

[0025] Mixing a transition metal salt, 2-methylimidazole and an organic solvent for coordination to obtain an imidazole metal organic framework compound; the transition metal salt includes a cobalt salt;

[0026] The imidazole metal organic framework compound and N-acetylglucosamine are mixed, and after segmented heat treatment in the presence of a fluorine source, carbonization is performed to obtain a carbon nanotube-carbon sheet-loaded transition metal fluoride composite material;

[0027] The staged heat treatment includes a first heat treatment and a second heat treatment performed sequentially; the temperature of the first heat treatment is 250-300°C; the temperature of the second heat treatment is 420-450°C.

[0028] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0029] The invention mixes transition metal salt, 2-methylimidazole and an organic solvent, and performs coordination to obtain an imidazole metal organic framework compound.

[0030] In the present invention, the transition metal salt includes a cobalt salt, and the transition metal salt preferably also includes one of a nickel salt, an iron salt and a zinc salt; the transition metal salt is preferably a nitrate.

[0031] When two transition metal salts are used in the present invention, the molar ratio of the cobalt salt to the other transition metal salt (ie, nickel salt, iron salt or zinc salt) is preferably 4-9:1.

[0032] In the present invention, the molar ratio of the transition metal salt to 2-methylimidazole is preferably 1:4-8, more preferably 1:5-6.

[0033] In the present invention, the organic solvent is preferably methanol; the usage ratio of the organic solvent to the transition metal salt is preferably 10 mL:1 mmol.

[0034] The present invention preferably adds a transition metal salt to a portion of the organic solvent to obtain a metal salt solution, adds 2-methylimidazole to the remaining organic solvent to obtain a 2-methylimidazole solution, and pours the 2-methylimidazole solution into the metal salt solution; the volume ratio of the portion of the organic solvent to the remaining organic solvent is preferably 1:1.

[0035] In the present invention, the coordination temperature is preferably room temperature, and the coordination time is preferably 12 to 24 hours, more preferably 16 to 18 hours.

[0036] After the coordination is completed, the present invention preferably washes the obtained product with ethanol and dries it at room temperature to obtain an imidazole metal organic framework compound, which is denoted as MIF.

[0037] After obtaining the imidazole metal organic framework compound, the present invention mixes the imidazole metal organic framework compound and N-acetylglucosamine, performs segmented heat treatment in the presence of a fluorine source, and then carbonizes to obtain a carbon nanotube-carbon sheet loaded transition metal fluoride composite material.

[0038] In the present invention, the imidazole metal organic framework compound and N-acetylglucosamine are preferably ground and mixed uniformly, and then placed in a tubular furnace, with another porcelain boat containing a fluorine source placed upstream.

[0039] In the present invention, the mass ratio of the imidazole metal organic framework compound to N-acetylglucosamine is preferably 1:4-8, more preferably 1:5-6.

[0040] In the present invention, the fluorine source preferably includes polytetrafluoroethylene; the mass ratio of the imidazole metal organic framework compound to the fluorine source is preferably 1:6-15, more preferably 1:10-12.

[0041] In the present invention, the staged heat treatment includes a first heat treatment and a second heat treatment performed sequentially; the temperature of the first heat treatment is 250-300°C, and the time of the first heat treatment is preferably 1-2 hours; the temperature of the second heat treatment is 420-450°C, and the time of the second heat treatment is preferably 2-3 hours.

[0042] In the present invention, the staged heat treatment and carbonization are preferably carried out under inert gas conditions, and the heating rate used is preferably 1-3°C / min, more preferably 2°C / min; the inert gas preferably includes nitrogen or argon.

[0043] Under the first heat treatment temperature, N-acetylglucosamine first melts and decomposes, and its oxygen-containing functional groups (negatively charged) are tightly combined with the nitrogen-containing functional groups (positively charged) of the MIF ligands, which can form a tight coating on MIF, and can be used as a carbon source and a nitrogen source, or as a sacrificial template to induce MIF to form a two-dimensional structure without the need for an external template agent. Under the second heat treatment temperature, the fluorine source begins to decompose, and a constant temperature allows it to decompose in small amounts for a long time, which helps to fully fluorinate and ensure the formation of carbon tubes.

[0044] In addition, the present invention uses N-acetylglucosamine to introduce heteroatoms such as nitrogen doping into the carbon material to achieve chemical adsorption of polysulfides and enhance the inhibitory effect of the shuttle effect.

[0045] In the present invention, the carbonization temperature is preferably 550-600°C, more preferably 600°C, and the time is preferably 2-4h, more preferably 3h. The present invention completes carbon tube growth and the formation of transition metal fluorides through carbonization to obtain a one-dimensional-two-dimensional structure of carbon nanotubes-carbon sheets loaded with transition metal fluorides.

[0046] The present invention loads an electrocatalyst (transition metal fluoride) on a carbon nanotube-carbon sheet, improves the conversion efficiency of polysulfide through catalysis, accelerates the conversion of polysulfide, and improves the performance of lithium-sulfur batteries.

[0047] The present invention provides a carbon nanotube-carbon sheet loaded transition metal fluoride composite material prepared by the preparation method described in the above technical solution.

[0048] The present invention provides application of the carbon nanotube-carbon sheet loaded transition metal fluoride composite material described in the above technical solution in a lithium-sulfur battery.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] Example 1

[0051] 2 mmol of cobalt nitrate was added to 20 mL of methanol to obtain a cobalt nitrate solution. 8 mmol of 2-methylimidazole was added to 20 mL of methanol to dissolve to obtain a 2-methylimidazole solution. The 2-methylimidazole solution was poured into the cobalt nitrate solution and allowed to stand at room temperature for 12 h. The obtained product was washed with ethanol and dried at room temperature to obtain Co-MIF.

[0052] 100 mg of the prepared Co-MIF and 400 mg of N-acetylglucosamine were ground and mixed evenly, and put into a tubular furnace. Another porcelain boat containing 600 mg of PTFE was placed upstream. Under nitrogen conditions, the temperature was raised to 250°C at a rate of 1°C / min and maintained for 1 hour. The temperature was then continued to be raised to 420°C and maintained for 2 hours. The temperature was then continued to be raised to 550°C and carbonized for 4 hours to obtain a one-dimensional to two-dimensional structure of carbon nanotubes-carbon sheets loaded with transition metal fluorides.

[0053] Example 2

[0054] 2 mmol of cobalt nitrate was added to 20 mL of methanol to obtain a cobalt nitrate solution. 16 mmol of 2-methylimidazole was added to 20 mL of methanol to dissolve to obtain a 2-methylimidazole solution. The 2-methylimidazole solution was poured into the cobalt nitrate solution and allowed to stand at room temperature for 24 h. The obtained product was washed with ethanol and dried at room temperature to obtain Co-MIF.

[0055] 100 mg of the prepared Co-MIF and 800 mg of N-acetylglucosamine were ground and mixed evenly, and put into a tubular furnace. Another porcelain boat containing 1500 mg of PTFE was placed upstream. The temperature was raised to 300°C at a rate of 3°C / min under argon conditions and maintained for 2 h. The temperature was then continued to be raised to 450°C and maintained for 3 h. The temperature was then continued to be raised to 600°C and carbonized for 2 h to obtain a one-dimensional to two-dimensional structure of carbon nanotubes-carbon sheets loaded with transition metal fluorides.

[0056] Example 3

[0057] 2 mmol of cobalt nitrate was added to 20 mL of methanol to obtain a cobalt nitrate solution. 8 mmol of 2-methylimidazole was added to 20 mL of methanol to dissolve to obtain a 2-methylimidazole solution. The 2-methylimidazole solution was poured into the cobalt nitrate solution and allowed to stand at room temperature for 24 h. The obtained product was washed with ethanol and dried at room temperature to obtain Co-MIF.

[0058] 100 mg of the prepared Co-MIF and 600 mg of N-acetylglucosamine were ground and mixed evenly, and put into a tubular furnace. Another porcelain boat containing 1000 mg of PTFE was placed upstream. The temperature was raised to 250°C at a rate of 2°C / min under nitrogen conditions and maintained for 2 h. The temperature was then continued to be raised to 420°C and maintained for 2 h. The temperature was then continued to be raised to 550°C and carbonized for 4 h to obtain a one-dimensional to two-dimensional structure of carbon nanotubes-carbon sheets loaded with transition metal fluorides.

[0059] Example 4

[0060] 1.6 mmol of cobalt nitrate and 0.4 mmol of nickel nitrate were added to 20 mL of methanol to obtain a mixed salt solution, and 8 mmol of 2-methylimidazole was added to 20 mL of methanol to dissolve to obtain a 2-methylimidazole solution, and the 2-methylimidazole solution was poured into the mixed salt solution and allowed to stand at room temperature for 16 hours. The obtained product was washed with ethanol and dried at room temperature to obtain CoNi-MIF;

[0061] 100 mg of the prepared CoNi-MIF and 600 mg of N-acetylglucosamine were ground and mixed evenly, put into a tube furnace, and another porcelain boat containing 1200 mg of PTFE was placed upstream. Under argon conditions, the temperature was raised to 300°C at a rate of 1°C / min and maintained for 1 hour, then continued to be raised to 420°C and maintained for 3 hours, and then continued to be raised to 600°C and carbonized for 3 hours to obtain a one-dimensional-two-dimensional structure of carbon nanotubes-carbon sheets loaded with transition metal fluorides.

[0062] Example 5

[0063] 1.8 mmol of cobalt nitrate and 0.2 mmol of zinc nitrate were added to 20 mL of methanol to prepare a mixed salt solution, and 10 mmol of 2-methylimidazole was added to 20 mL of methanol to dissolve to obtain a 2-methylimidazole solution, and then the 2-methylimidazole solution was directly poured into the mixed salt solution, and allowed to stand for 12 hours. The obtained product was washed with ethanol and dried at room temperature to obtain CoZn-MIF;

[0064] 100 mg of the prepared CoZn-MIF and 400 mg of N-acetylglucosamine were ground and mixed evenly, and put into a tubular furnace. Another porcelain boat containing 1000 mg of PTFE was placed upstream. The temperature was raised to 300°C at a rate of 1°C / min under argon conditions and maintained for 1 hour. The temperature was then continued to be raised to 450°C and maintained for 2 hours. The temperature was then continued to be raised to 550°C and carbonized for 3 hours to obtain a one-dimensional to two-dimensional structure of carbon nanotubes-carbon sheets loaded with transition metal fluorides.

[0065] Characterization

[0066] 1) Figure 1SEM image of CoF2 supported on one-dimensional and two-dimensional carbon nanotube-carbon sheet in Example 3; It can be seen from Figure 1 that a large number of one-dimensional carbon nanotubes are attached to the prepared two-dimensional flake material.

[0067] 2) Figure 2 XRD pattern of CoF2 supported on one-dimensional and two-dimensional carbon nanotube-carbon sheet in Example 3; It can be seen from Figure 2 that the species of metal compound in the synthesized material is CoF2.

[0068] Application test

[0069] Battery assembly method: Preparation of sulfur cathode: Sublimed sulfur and the materials prepared in Examples 1-5 were mixed at a mass ratio of 3:1, and heated in an ampoule at 155 °C for 12 h. The obtained mixture was dispersed in NMP with carbon nanotubes and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. The obtained slurry was coated on aluminum foil and dried at 60 °C for 8 h.

[0070] The obtained sulfur cathode, functional separator, lithium metal anode and commercial electrolyte (1.0 M LiTFSI in DME:DOL = 1:1 Vol% & 2% LiNO3) were assembled into a CR2016 coin-type battery in a glove box filled with argon. Before the electrochemical test, the battery was allowed to stand for 8 h, and the battery performance was tested at 0.2C.

[0071] The results show that under the test conditions of 0.2C, the specific capacities of the carbon nanotube / carbon sheet supported transition metal fluorides prepared in Examples 1-5 are 1205 mAh·g -1 , 1176 mAh·g -1 , 1316 mAh·g -1 , 1301 mAh·g -1 and 1196 mAh·g -1 .

[0072] Figure 3 Charge-discharge curve of the battery composed of the one-dimensional and two-dimensional carbon nanotube / carbon sheet supported CoF2 material in Example 3. It can be seen from Figure 3 that there are two voltage platforms in the voltage-capacity curve during the discharge process at about 2.30 V and 2.10 V, corresponding to the two processes of the ring-opening of cyclic S8 molecules to form long-chain polysulfide lithium (Li2S n , 4 < n < 8) and the reaction of long-chain polysulfide lithium to form short-chain polysulfide lithium (Li2S n , n ≤ 2) during the battery discharge process.

[0073] In addition, the battery composed of the one-dimensional-two-dimensional carbon nanotube / carbon sheet loaded CoF2 material in Example 3 was subjected to rate cycle charge and discharge tests at current densities of 0.2C, 0.5C, 1C, 2C, 1C, and 0.5C. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the specific capacity at each current density after cycling can still reach 1253 mAh g -1 、1123mAh·g -1 、1062mAh·g -1 、931mAh·g -1 、1092mAh·g -1 and 1137mAh·g -1 , indicating that the material has good rate performance and cycle stability.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carbon nanotube-carbon sheet-loaded transition metal fluoride composite material, comprising the following steps: Mixing a transition metal salt, 2-methylimidazole and an organic solvent for coordination to obtain an imidazole metal organic framework compound; the transition metal salt includes a cobalt salt; The imidazole metal organic framework compound and N-acetylglucosamine are mixed, and after segmented heat treatment in the presence of a fluorine source, carbonization is performed to obtain a carbon nanotube-carbon sheet-loaded transition metal fluoride composite material; The staged heat treatment includes a first heat treatment and a second heat treatment performed sequentially; the temperature of the first heat treatment is 250-300°C; the temperature of the second heat treatment is 420-450°C.

2. The preparation method according to claim 1, characterized in that: The transition metal salt further comprises one of a nickel salt, an iron salt and a zinc salt.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the transition metal salt to 2-methylimidazole is 1:4-8.

4. The preparation method according to claim 1, characterized in that: The coordination temperature is room temperature and the coordination time is 12 to 24 hours.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the imidazole metal organic framework compound to N-acetylglucosamine is 1:4-8.

6. The preparation method according to claim 1, characterized in that: The fluorine source includes polytetrafluoroethylene; the mass ratio of the imidazole metal organic framework compound to the fluorine source is 1:6-15.

7. The preparation method according to claim 1, characterized in that: The time of the first heat treatment is 1 to 2 hours; the time of the second heat treatment is 2 to 3 hours.

8. The preparation method according to claim 1, characterized in that: The carbonization temperature is 550-600° C. and the time is 2-4 hours.

9. The carbon nanotube-carbon sheet-loaded transition metal fluoride composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon nanotube-carbon sheet loaded transition metal fluoride composite material according to claim 9 in a lithium-sulfur battery.